Analisis Faktor-Faktor Penyebab Turunnya Penyaluran Kredit Cepat Aman (KCA) pada PT Pegadaian (Persero) UPC Pasar Pagi - Vani Daun Limbong; Elisabet Pali; Abedneigo C. Rambulangi (Universitas Kristen Indonesia Toraja, 2025)
This study aims to identify and describe the factors contributing to the decline in the distribution of Kredit Cepat Aman (KCA) at PT Pegadaian (Persero), Pasar Pagi Service Unit, during the period of January 2022 to December 2024. This research employs a descriptive qualitative method with a case study approach, involving purposively selected informants consisting of the unit manager, appraisers, and customers. Data were collected through in-depth interviews, participatory observations, and documentation analysis (KCA realization data from 2022 to 2024). The data were analyzed using thematic analysis through the stages of data reduction, data display, and conclusion verification/triangulation. The results indicate that the decline in KCA distribution is influenced by internal factors including interest rate (service fee) policies, collateral appraisal standards, credit provision procedures, non-performing loan ratios, service quality, and marketing activities as well as external factors such as competition among financial institutions, fluctuations in collateral prices, product availability, and local economic conditions affecting community purchasing power. These findings suggest the need for improvements in collateral appraisal procedures, enhancements in service quality and localized marketing strategies, and adjustments to interest rate policies that are responsive to local economic dynamics in order to restore and increase KCA distribution performance.